2014
DOI: 10.1039/c4ra03137g
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted organocatalytic synthesis of 5-hydroxymethyl furfural in a monophasic green solvent system

Abstract: Monophasic microwave assisted dehydration of fructose to 5-hydroxymethyl furfural (HMF) catalyzed by p-toluene sulphonic acid (PTSA) was studied in non-aqueous organic solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
0
18
1
Order By: Relevance
“…However, the use of DMF and DMSO is not ecologically favorable and is energy inefficient due their high boiling points, which makes separation complicated. Our previous study demonstrated the use of IPA as an efficient solvent system that also afforded easy separation in the presence of the homogeneous catalyst p ‐toluenesulfonic acid (PTSA) . In the case of heterogeneous catalysis, both the selectivity of the catalyst and reaction solvent play important roles .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the use of DMF and DMSO is not ecologically favorable and is energy inefficient due their high boiling points, which makes separation complicated. Our previous study demonstrated the use of IPA as an efficient solvent system that also afforded easy separation in the presence of the homogeneous catalyst p ‐toluenesulfonic acid (PTSA) . In the case of heterogeneous catalysis, both the selectivity of the catalyst and reaction solvent play important roles .…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated the use of IPAa sa ne fficient solvents ystem that also afforded easy separationi nt he presence of the homogeneous catalyst ptoluenesulfonic acid (PTSA). [30] In the case of heterogeneous catalysis, both the selectivityo ft he catalyst and reaction solvent play important roles. [46] Theu se of low-boiling solvents for the heterogeneous catalytic production of 5-HMF has generally failed to give yields higher than 80 %.…”
Section: Influence Of Solventmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, the renewable isopropanol (i-PrOH) was found to be effective to mediate the dehydration reaction efficiently to produce HMF. 25,26 It has low boiling point and low environmental toxicity, and thus enables a simple production and isolation of HMF, and offers a new opportunity for a large-scale economically viable process. 24,27 Hence, the i-PrOH will be a promising environment-friendly solvent for HMF production with the LiCl additive.…”
Section: Introductionmentioning
confidence: 99%
“…S8 †). 55 This peak is absent in C20 which indicates the absence of 5-HMF due to complete degradation to the furan derivatives with increased microwave time. Moreover, 5-HMF could be quantied by LC-MS analysis and the abundance of 5-HMF in C5, C10 and C15 is 93, 89 and 9%, respectively.…”
Section: Characterization Of the C-dots And G-dotsmentioning
confidence: 98%